Metachronous Contralateral Male Breast Cancer: Case Report and Literature Review. Issue 9 (2nd April 2019) - O'Leary, Thomas R; Shriver, Craig D; Wind, Gary
Abstract: Male breast cancer (MBC) is rare and consequently understudied. Here we present the case of contralateral breast cancer in a male patient nearly a quarter century following his initial breast cancer diagnosis and treatment. The epidemiology, risk factors, diagnosis, characterization, treatment, and prognosis of male breast cancer are reviewed. MBC accounts for <1% of all breast cancer with an estimated incidence nearly 1.25 per 100, 000 person years. Our patient tested positive for ATM mutation of undetermined significance. More commonly in males, a BRCA 2 mutation confers a >1 in 15 lifetime risk of breast cancer and is present in >11% of MBC patients, while BRCA 1 is present in an estimated <1.5% of MBC patients. The risk of contralateral breast cancer developing in a male with a unilateral lesion is much higher than for a primary male breast cancer in the general population. Men tend to be diagnosed at a later age and stage than females. Prognosis for male and female breast cancer is similar considering both age of patient and stage of the tumor at diagnosis, and similar treatment paradigms have resulted in similar outcomes. Although lumpectomy with radiation therapy may have the same prognosis as mastectomy, the standard of care for male breast cancer continues to be simple mastectomy with sentinel lymph node biopsy.